Improving Students' Listening Ability Using Edpuzzle Interactive Video - Nadrotin Mawaddah; Mutmainnah Mustofa; Irfan Susiyana Putra (Premise: Journal of English Education and Applied Linguistics, 2022)
The problems faced by the students in this listening class were identified as the difficulty of recalling memory and managing concentration during listening. Therefore, this classroom action research solution is Edpuzzle interactive video because the teacher can easily embed questions, notes, and recording voices into the video. When students play the video until it reaches a particular minute of the timeline, it will automatically pause, and a question will appear. This study revealed that this media could increase the students' listening skills. The students were more motivated to listen using Edpuzzle because they liked the "rewatch" feature and the automatic feedback. The teacher's role in presenting a clear tutorial and directing the listening process is crucial to the success of this research. Moreover, the teacher paid more attention to the content of the video and the complexity of the questions adjusted to the students' listening ability level.